Physical and Mental Aspects of Quality of Life in Patients With Charcot-Marie-Tooth Disease Type 1A - Ivanovic, Vukan; Bjelica, Bogdan; Palibrk, Aleksa; Brankovic, Marija; Bozovic, Ivo; Basta, Ivana; Savic, Andrija; Stojanovic, Vidosava Rakocevic; Kacar, Aleksandra (Frontiers in Neurology, 2022)
Introduction Charcot-Marie-Tooth type 1A (CMT1A) comprises ~50% of all CMT cases. CMT1A is a slowly progressive motor and sensory neuropathy that leads to significant disability. We aimed to investigate the quality of life (QoL) in Serbian patients with CMT1A and to assess sociodemographic and clinical features associated with their QoL. Material and Methods Forty-five genetically confirmed patients with CMT1A were included −60% women [age 50.4 ± 12.6 years, disease duration 22 (12.5–31.5) years]. SF-36, Medical Research Council (MRC) Sum Score, CMT Examination Score (CMTES), Overall Neuropathy Limitation Scale (ONLS), Beck Depression Inventory (BDI), and Krupp's Fatigue Severity Scale (FSS) were used in the study. Results Regarding SF-36, Mental Health and Social Functioning were the scales with the best achievements, whereas Role Physical was the worst domain. Worse QoL in patients with CMT1A was associated with elder age (rho = −0.34, p < 0.05), longer disease duration (rho = −0.31, p < 0.05), more pronounced muscle weakness measured by MRC-SS (rho = 0.43, p < 0.01), presence of tremor (p < 0.05), worse CMTES (rho = −0.68, p < 0.01), more severe disability in upper (rho = −0.70, p < 0.01) and lower limbs (rho = −0.61, p < 0.01) measured by ONLS scores, use of walking aids (p < 0.01), and with depression (p < 0.01) and fatigue (p < 0.01). Worse scores on CMTES (beta = −0.43, p < 0.01), BDI (beta = −0.39, p < 0.01), and FSS (beta = −0.36, p < 0.01) were significant independent predictors of worse QoL in patients with CMT1A (adjusted R2 = 0.77, p < 0.001). Conclusion Besides impairment made directly by CMT1A itself, QoL in these patients was also strongly affected by the presence of depression and fatigue. Since CMT1A is still not a curable disease, it is of interest to identify factors associated with QoL that are amenable to treatment.